Leaf–Root–Soil Stoichiometric Characteristics in Different Shrub Ages of Ammopiptanthus mongolicus - Xue Dong; Dehao Xu; Danyang Wang; Chunxia Han; Yaru Huang; Jingbo Zhang (Plants, 2023)
The ecological indicators for the growth and restoration of A. mongolicus populations are important for grasping the regulatory mechanisms of the biogeochemistry cycle, and for providing basic data for the prediction and evaluation of the evolution characteristics of natural A. mongolicus populations. We conducted studies on the eco-stoichiometric characteristics of natural A. mongolicus in different shrub ages, in order to understand the nutrient limitations for the growth and development of A. mongolicus and the synergy between the soil, leaves and roots, and to explore the C, N and P stoichiometric characteristics on A. mongolicus. The results showed the following: (1) The response of C, N and P stoichiometric characteristics in the leaves, roots and soil to changes in shrub age was not completely consistent. The leaf C content was young shrub> mature shrub> middle age shrub. The C content in the root system and C and N content in the soil showed an upward trend with increasing shrub age. The N and P contents of the root system and the P content of the soil showed a downward trend with increasing shrub age. The stoichiometric ratios C:N, C:P and N:P in the leaves, roots and soil showed an upward trend, and the N:P ratios in the leaves and roots were similar. (2) Among the stoichiometric characteristics of the leaves, C, N and P, leaves P and C:P are the most sensitive to shrub age changes, and have ecological implications for the growth and population dynamics of A. mongolicus. The average N:P ratios of young A. mongolicus leaves in young, middle-aged and mature shrubs were 15.32, 18.23 and 21.76, respectively. It can be seen that with an increase in shrub age, the growth of A. mongolicus gradually shifted from being jointly restricted by N and P to being more restricted by P. (3) The N content and the C∶N and N∶P ratios of A. mongolicus are classified as “strictly homoeostasis “, which shows strong plant homoeostasis for environmental adaptability. The N supplemented by symbiotic nitrogen fixation makes A. mongolicus have strong N internal homoeostasis. Therefore, in a desert grassland with low N content, the growth process of A. mongolicus may be easily restricted by P due to the additional N absorbed by it. (4) The C, N and P contents of the leaves, roots and soils of the three shrubs were shown as leaf > root > soil, and the difference was significant (p < 0.05). The correlation analysis showed that the C, N and P contents of the soil, roots and leaves and their stoichiometric ratio characteristics of the three shrubs showed a certain correlation. Among them, the P content of the soil was significantly related to the N:P ratio of the leaves and roots. Therefore, P is likely to become a limiting factor in the plant growth and repair process of the plant ecosystem in the A. mongolicus population. In summary, during the growth of A. mongolicus, special attention should be paid to the balance of nutrients. In order to improve its productivity, it is recommended to reasonably apply P fertilizers in the process of tending management to enhance the soil nutrient status and improve plant nutrient utilization efficiency and homoeostasis.